Diabetes mellitus among adult survivors of childhood acute lymphoblastic leukemia: A report from the St. Jude Lifetime Cohort Study. Issue 4 (12th November 2019) - Williams, Hannah E.; Howell, Carrie R.; Chemaitilly, Wassim; Wilson, Carmen L.; Karol, Seth E.; Nolan, Vikki G.; Smeltzer, Matthew P.; Green, Daniel M.; Ehrhardt, Matthew J.; Mulrooney, Daniel A.; Pui, Ching‐Hon; Hudson, Melissa M.; et al.
Abstract : Background: Greater than one‐half of children who are treated for acute lymphoblastic leukemia (ALL) develop ≥1 treatment‐related medical conditions in their lifetime, many of which are known risk factors for diabetes mellitus. In the current study, the authors evaluated the prevalence and risk factors of diabetes mellitus among clinically assessed adult survivors of childhood ALL Methods: The authors performed a retrospective evaluation of data from survivors of ALL and community controls who were enrolled in the St. Jude Lifetime Cohort Study between October 1, 2007, and June 30, 2016. Participants were adults with ≥10 years of survival of childhood ALL and community controls who completed clinical and laboratory evaluations. Data for the current analysis were abstracted from medical records. Exposures evaluated herein included chemotherapy and radiation exposures and medical history, including drug‐induced diabetes mellitus. Results: Of 1360 eligible adults who were ≥10‐year survivors of childhood ALL, a total of 1044 completed the evaluations; these individuals had a mean age of 33.97±9.14 years and 50.86% were male. The 368 controls, 45.65% of whom were male, had a mean age of 35.33±10.21 years. Type 2 diabetes mellitus (T2DM) was found in approximately 7.47% of survivors and 3.80% of controls (odds ratio [OR], 2.07; 95% CI, 1.11‐3.87). In adjusted models, among survivors, older age (OR, 1.05 for each additional year; 95% CI, 1.02‐1.08), body mass index ≥30 kg/m 2 (OR, 7.40; 95% CI, 2.61‐20.97), and drug‐induced diabetes mellitus occurring during ALL therapy (OR, 4.67; 95% CI, 2.53‐8.61) were found to be associated with T2DM. Conclusions: Adult survivors of childhood ALL are at an increased risk of T2DM. Adult survivors of childhood ALL who are of older age, with an overweight or obese body mass index, and/or who developed drug‐induced diabetes mellitus during treatment should be closely monitored for T2DM during long‐term follow‐up. Abstract : The results of the current study demonstrate a high prevalence of clinically ascertained diabetes in adult survivors of childhood acute lymphoblastic leukemia. These data identify an association between the occurrence of drug‐induced diabetes during therapy and the development of future diabetes.